Odpowiedź :
Ustal wartość m i n.
a) (7³/5²)^3*(5³/7⁵)⁴=(7⁹/5⁶)*(5¹²/7²⁰)=5m/7n=5⁶/7¹¹
m=6, n=11
b) (16/25)⁴*(5/8)³=(2⁴/5²)⁴*(5/2³)³=(2¹⁶/5⁸)*(5³/2⁹)=2n/5m=2⁷/5⁵
n=7, m=5
a) (7³/5²)^3*(5³/7⁵)⁴=(7⁹/5⁶)*(5¹²/7²⁰)=5m/7n=5⁶/7¹¹
m=6, n=11
b) (16/25)⁴*(5/8)³=(2⁴/5²)⁴*(5/2³)³=(2¹⁶/5⁸)*(5³/2⁹)=2n/5m=2⁷/5⁵
n=7, m=5
a )(7³/5²)³ × (5³/7^5)^4 = 5^m/7^m
7^9/5^6 * 5^12/ 7^20 = 7^9/5^6 ÷ 7^20/ 5^12 = 7^9-20 / 5^ 6-12 = 7^-11 / 5^-6
7^-11 / 5^-6 = 5^m/7^m <=> 5^6/7^11= 5^m/7^n <=> m = 6 n =11
b)
7^9/5^6 * 5^12/ 7^20 = 7^9/5^6 ÷ 7^20/ 5^12 = 7^9-20 / 5^ 6-12 = 7^-11 / 5^-6
7^-11 / 5^-6 = 5^m/7^m <=> 5^6/7^11= 5^m/7^n <=> m = 6 n =11
b)